Pengaruh Brand Trust dan Brand Awareness terhadap Purchase Decision di Kopi Kenangan Garut (Studi Kasus Generasi Z di Garut Kota) - Mohamad Rafie Eka Putra; Della Azmiatul Khoiriah; Mochamad Agil; Sakinah Aulia Antasari (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The rapid growth of the modern coffee industry in Indonesia has intensified brand competition, particularly in efforts to build brand trust and brand awareness as factors influencing Generation Z’s purchasing behavior. This study aims to analyze the effect of brand trust and brand awareness on purchase decisions for Kopi Kenangan products in the Garut region. A quantitative approach with a descriptive and associative research design was employed. Data were collected through questionnaires distributed to 96 Generation Z respondents who had purchased Kopi Kenangan at least three times, using a purposive sampling technique. The collected data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that both brand trust and brand awareness have a positive and significant effect on purchase decisions. However, brand awareness demonstrates a stronger influence than brand trust. These findings suggest that consumers’ ability to recognize and recall a brand serves as the primary determinant in driving Generation Z’s purchase decisions, while brand trust functions as a supporting factor that strengthens consumer confidence. This study contributes theoretically to the development of consumer behavior research in the modern coffee industry and provides practical implications for companies in formulating marketing strategies that emphasize strengthening brand awareness and brand trust.trust.